2019
DOI: 10.1038/s41467-019-10865-y
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus evades antibody-mediated immunity through endoplasmic reticulum-associated degradation of the FcRn receptor

Abstract: Human cytomegalovirus (HCMV) can persistently infect humans, but how HCMV avoids humoral immunity is not clear. The neonatal Fc receptor (FcRn) controls IgG transport from the mother to the fetus and prolongs IgG half-life. Here we show that US11 inhibits the assembly of FcRn with β 2 m and retains FcRn in the endoplasmic reticulum (ER), consequently blocking FcRn trafficking to the endosome. Furthermore, US11 recruits the ubiquitin enzymes Derlin-1, TMEM129 and UbE2J2 to engage FcRn, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…Moreover, Liu et al recently reported that CMV is able to downregulate the neonatal Fc receptor, involved in albumin level maintenance via US11. This might influence the relationship between CMV replication and serum albumin [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liu et al recently reported that CMV is able to downregulate the neonatal Fc receptor, involved in albumin level maintenance via US11. This might influence the relationship between CMV replication and serum albumin [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgA and IgG play a major role in mucosal infection immunity; some cytokines or pathogens have also evolved ways to regulate pIgR and FcRn to facilitate infection [29,30]. Reovirus, LPS (a ligand for Toll-like receptor 4 (TLR4) TLR4), IFN-γ, and tumor necrosis factor-alpha (TNF-α) all regulate pIgR and FcRn expression, mainly by the activation of the NF-κB or Janus kinase/signal transducers and activators of transcription (JAK-STAT) JAK-STAT pathway [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of FcRn and pIgR by reovirus have been shown in the tracheal mucosa of simian-human immunodeficiency virus/simian immunodeficiency virus (SHIV/SIV)-infected rhesus monkeys [35,36]. Human cytomegalovirus evades humoral immunity by the degradation of FcRn [30]. TGEV-induced FcRn expression by activating NF-κB signaling in porcine small intestinal epithelial (IPEC-J2) cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gp68 86 , gp34 87 , gpRL13, and gp95 88 , 89 , were found to be expressed on the membrane surface of HCMV infected cells, and bind to the Fc segment of IgG on the membrane 85 , resulting in the inability of FcγRIIIA receptor on NK cells to bind to the antibody on the target cells and hinder the bridge between cellular immunity and humoral immunity 90 , 91 . One study proposed that the HCMV glycoprotein US11 inhibits neonatal Fc receptor functions (FcRn), causing its degradation in the endoplasmic reticulum, which may dampen mucosal and maternal immunity and reduce IgG half-life in blood and tissues, ultimately helping HCMV to escape antibody-mediated immunity 92 .…”
Section: The Immune Escape Mechanism Of Hcmvmentioning
confidence: 99%